The effect of pretreatment using hydrochloric acid on the characteristics of buffalo hide gelatin - Mulyani, S.; Setyabudi, F. M. C. S.; Pranoto, Y.; Santoso, U. (Diponegoro University, 2017)
The objective of the research was to identify the effect of the concentration of hydrochloric acid (HCl) on yield and the characteristics of gelatin from buffalo hide. A completely randomized design was used with various concentrations of HCl treatment 0.3M, 0.6M, 0.9 M, 1.2 M and 1.5M, and four times replication, followed by least significant difference test. The HCl concentration gave significantly effect (P<0.05) on yield, viscosity, pH, gel strength and redness of gelatin. The highest yield (29.17%) was obtained at a concentration of HCl 0.9M. The highest gel strength and viscosity at concentration of 1.2M, were 293.41g bloom and 22.17 cp, respectively. The pH of the gelatin were 5.08 to 5.52. The lightness level (L*) was 69.92-70.97, whereas the redness ranged (a*) from 0.55 to 1.54 and the yellowness ranged (b*) from 17.54 to 19.59. The moisture, protein and ash concentrations of gelatin were 7.05±0.07-8.92±0.06%, protein content of 83.38±0.06 -91.11±0.03%, and the ash content 0.53 ± 0.04 to 1.23 ± 0.09%, respectively. Based on the spectra absorption of infrared were detected four areas amides: amide A (3402.43-3448.72 cm-1), amide I (1635.65 cm-1), amide II (1527.62 cm-1) and amide III (1242.16 cm-1). The differences in the concentration of HCl had impact on yield,characteristics and secondary structure of buffalo hide gelatin. The HCl concentration at 0.9M was the optimum condition to obtain the highest yield. The characteristics of buffalo hide gelatin after pretreatment using hydrochloric acid had met the standards of GMIA (2012).